2020
DOI: 10.1101/2020.04.14.038893
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relaxation of purifying selection suggests low effective population size in eusocial Hymenoptera and solitary pollinating bees

Abstract: Eusociality is a rare life history strategy that evolved repeatedly in Hymenoptera. At the population genetics level, inbreeding and low effective population size have been suggested as both evolutionary causes and consequences of social life. In this study, we tested these hypotheses by estimating the relative rate of non-synonymous substitution in 169 species to investigate the variation in natural selection efficiency and effective population size throughout the Hymenoptera tree of life. We show that relaxe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
2
4
0
Order By: Relevance
“…Consistent with several previous studies in social spiders (33, 3639) and social insects (26, 57, 58), we found that social branches tend to experience elevated genome-wide rates of molecular evolution (i.e. dN/dS) compared to nonsocial branches.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with several previous studies in social spiders (33, 3639) and social insects (26, 57, 58), we found that social branches tend to experience elevated genome-wide rates of molecular evolution (i.e. dN/dS) compared to nonsocial branches.…”
Section: Discussionsupporting
confidence: 92%
“…1A), which might be explained by lineage-specific differences in effective population size or other factors. Similarly, in a previous study in hymenopteran insects, social branches experienced elevated genome-wide dN/dS compared to nonsocial branches, but most variation existed between lineages, with bees --regardless social organization --having the highest dN/dS (58).…”
Section: Discussionsupporting
confidence: 58%
“…Using a previously published phylogenomic dataset containing 3256 genes and 169 hymenopteran species (Peters et al 2017), Weyna and Romiguier (2021) estimated mean genomic dN/dS ratios (nonsynonymous to synonymous substitution rates) for each species and compared these values between parasitic and nonparasitic species, eusocial and solitary species, and in relation to body size, parasitoid-specific traits and geographic range, thought to affect the effective population size and strength of selection. The use of a large number of species, as well as several distinct traits is a clear asset of this study.…”
Section: Published: 05 Feb 2021mentioning
confidence: 99%
“…
Relaxation of purifying selection suggests low effective population size in eusocial Hymenoptera and solitary pollinating bees (2021( ), bioRxiv, 2020 peer-reviewed and recommended by Peer Community in Evolutionary Biology.
…”
mentioning
confidence: 99%
See 1 more Smart Citation